The comparative study relationship between coping strategies and (Drug Control Headquarters, Research and Education Office, 2008)
Objectives: The present article has been carried out the relationship between coping strategies and attitude to drug in drug users. Methods: The research method is descriptive (causal-comparative).The sample includes 100 men (50 addicted and 50 non addicted mea) Aged 20-34 years old. Tools of research were two questionnears: 1- Coping strategies inventory (Carror, Shirer & Wintrab) containing 72 questions with 0.63 - 0.95 reliability. 2- Other attitudes toward drug measurement contained 20 questions whose reliability is 0.73. The statistical tests used in this research were T- TEST and K-square. Findings: Analyzing the data indicated a significant difference between coping strategies and attitude toward drug. Results: Results: Regarding x2=36.2,P<./..., the suggestion of preventive interventions specially teaching coping strategies is appropriate abilities for stressful situations are useful for achieving healthy life style.